Effects of an Intraoperative Intravenous Bolus Dose of Dexmedetomidine on Remifentanil-Induced Postinfusion Hyperalgesia in Patients Undergoing Thyroidectomy: A Double-Blind Randomized Controlled Trial. (25th June 2020) - Wu, Zhijie; Yu, Junjie; Lin, Qihua; Li, Huiting; Zhang, Tianhua; Tan, Hongying; Lin, Wenqian; Cao, Longhui
Abstract : BACKGROUND: Consecutive exposure to high-dose remifentanil during anesthesia may induce remifentanil-induced postinfusion hyperalgesia (RPH). Dexmedetomidine, a highly selective α2-adrenergic receptor agonist, may have synergistic effects with opioids and aid in perioperative pain management. In this study, we hypothesized that an intraoperative bolus dose of intravenous dexmedetomidine could alleviate RPH in patients undergoing thyroidectomy under general anesthesia. METHODS: Ninety patients undergoing thyroidectomy were randomly assigned to 1 of 3 groups: placebo, normal saline (group P); low-dose dexmedetomidine 0.2 μg·kg −1 (group LD); or high-dose dexmedetomidine 0.5 μg·kg −1 (group HD). Remifentanil was infused at a rate of 0.30 μg·kg −1 ·minute −1 . Mechanical pain thresholds were measured using an Electronic von Frey device preoperatively and at 30 minutes, 6 hours, 24 hours, and 48 hours after surgery and were analyzed with 2-way repeated-measures analysis of variance (ANOVA) followed by Bonferroni post hoc comparison. We also recorded postoperative pain scores, the incidence of receiving rescue analgesics, and side effects up to 48 hours after surgery. RESULTS: The mechanical pain thresholds around the skin incision were significantly higher in group LD compared to group P 30 minutes and 6 hours after surgery (mean ± standard deviation: [65.0 ± 25.2] vs [49.6 ± 24.4] g, mean difference [95% confidence interval]: 15.4 [0.3–30.5] g, P = .045 at 30 minutes; [65.9 ± 24.5] vs [49.3 ± 26.1] g, 16.6 [1.1–32.1] g, P = .032 at 6 hours). The pain thresholds around the skin incision were significantly higher in group HD compared to group P 30 minutes and 6 hours after surgery ([67.8 ± 21.7] vs [49.6 ± 24.4] g, 18.2 [3.1–33.3] g, P = .013 at 30 minutes; [68.3 ± 22.5] vs [49.3 ± 26.1] g, 19.0 [3.5–34.5] g, P = .011 at 6 hours). The incidence of hyperalgesia around the skin incision was lower in group HD than in group P 30 minutes and 6 hours after surgery (4 [13%] vs 14 [48%], P = .012 at 30 minutes, 4 [13%] vs 12 [41%], P = .045 at 6 hours), although no significant difference was observed between group LD and group P. Postoperative pain scores, the incidence of rescue analgesic demand, and postoperative side effects were not significantly different between the groups. CONCLUSIONS: An intraoperative intravenous bolus dose of dexmedetomidine 0.5 μg·kg −1 alleviates remifentanil-induced hyperalgesia in patients undergoing thyroidectomy without a significant difference in side effects.